(3GdeYjf TQM GdTGWHjIs - (3EeGe eMeO Hf MSGe OQg GdGHGJdhZj GdMfajs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdEfSGf hdeG cGf GdbQBf GdYXje CYXe cJGH CfRd hdeG cGf MQR GdCeGfj aj hLg GdJgGfj s
(3BNQgG (B:s
(3EPG hbY THgI EJUGd CMO eeG HGdBNQI eY GdQeR s
(3GdfSNI HgG MhGTs
(3MQR GdCeGfi hhLg GdJgGfi GdeYQhaI HGdTGWHjI GfXQ cTa GdXfhf L (B1 (3U`(B646s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
Keywords: (3GdbQGAGJ hGdJLhjOs